TOLERANSI TANAMAN KEDELAI TERHADAP CEKAMAN AIR : AKUMULASI PROLIN DAN ASAM ABSISIK DAN HUBUNGANNYA DENGAN POTENSIAL OSMOTIK DAUN DAN PENYESUAIAN OSMOTIK - Didy Sopandie; , Hamim; Muhammad Jusuf; Nani Heryani (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1996)
In this experiment. the changes on leaf osmotic potential and accumulation of proline and abscisic acid were identified from drought-tolerant and drought - sensitive soybean genotypes. Three drought - tolerant (Mlg 2805, Mlg 2984 and Mlg 2999) and two sensitive soybean genotypes (Mlg 2510 and Mlg 3541) were subjected to drought condition created by regulating water supply in greenhouse. The results revealed that exposing plants to drought stress brought about a decrease of leaf osmotic potential. The decrease of which was greater in drought-tolerant genotypes (6.91 to 10.11 bars) than in sensitive genotypes (0.55 to 0.69 bars). The decreasing of leaf osmotic potential was followed with increasing praline accumulation, especialy for Mlg 2805. Only Mlg 2805 showed the significant ABA accumulation when the plants were subjected to drought stress. It is suggested that the drought tolerance was associated with the reduction of leaf osmotic potential (osmotic adjusment) in which proline might play an important role. The role of ABA could not be clarified since there had been a great variability in ABA content of all tolerant genotypes.